Managing Coach-Athlete Dynamics: Immediacy and Meta-Perception in Intercollegiate Sports - Erica Pasquini; Lindsey Blom; James Johnson; Adam Smith; Lawrence W Judge (Journal of Applied Sports Management, 2024)
This study investigates the correlation between intercollegiate athletes' meta-perception accuracy and their assessment of coaches' immediacy behaviors, and actions that foster closeness. Utilizing the Coach-Athlete Relationship Questionnaire, 54 athletes evaluated their coaches' immediacy. Findings indicate that lower meta-accuracy aligns with perceived lower immediacy, highlighting the role of perceived relational closeness in athlete self-awareness. Gender dynamics, in terms of coach-athlete dyads, exhibited no effect on meta-perception accuracy. The findings of the study lend credence to sport managers including immediacy behaviors in coach training to enhance athletes' meta-accuracy perception, while also contributing to the literature on meta-perception in sports and coach-athlete gender dynamics.
Keywords: meta-perception accuracy; coach-athlete relationship; immediacy behaviors; empathic accuracy